CEO Characteristics Influence on CEO Duality: Evidence from the Philippines - Lizares, Regina (Philippine Management Review; Vol 31 (2024), 2024)
This study investigates the influence of chief executive officers’ (CEO) demographic characteristics on the likelihood of CEO duality on boards of Philippine publicly listed corporations (PLCs). It draws on the competing perspectives of agency and stewardship, as well as human capital and upper echelon theories. It uses logistic regression on a sample of 252 active PLCs as of the end of 2021. Results indicate 30% of Philippine PLCs continue to practice CEO duality, despite the recommendation of the 2016 Code of Good Governance for Philippine PLCs to separate the roles of CEO and chairman of the board (COB). It also demonstrates that the likelihood of CEO duality is influenced by gender, tenure, and age; that is, an older, longer tenured man has more chances to hold both the position of CEO and COB. This supports the idea that CEO duality choice is associated with experience-based human capital.